ERIODISASI SENI UKIR KARYA I MADE SUTHEDJA - I Wayan Sudana (SURYA SENI, 2008)
Period of I Made Suthedja’s Craft Art. Suthedja’s style changes can be categorized into three main parts, which are: the ﬁ rst period (1960–1970), his  styles were mainly togog-shaped three-dimensional ﬁ gures made of ebben wood.The second period (1971-1989), at this time the moment his style changed into two-dimensional classical-modern reliefs made of teak or sometimes  exhibited in frames. The third period (1990–2004) his works are two-dimensional freereliefs using second-hand wood and are exhibited without any frames.   Suthedja’s style changes is inﬂ uenced by several factors. These factors are crisis and material condition, his formal and non-formal education, ﬁ ne arts growth modern Bali, his person experience, cultural social environment, and motivation or personal ambitions, Keywords : changes, art works, and Artisan.